The Impact of Islamophobia on Society, Attitudes, Policies and The Youths - Ismail Adaramola Abdul Azeez; Amidu Adinoyib Jimoh (Eduvest - Journal of Universal Studies, 2023)
Is Islamophobia a new marvel?. Are Islam and the Judeo-Christian West still hateful of and hostile toward each other? What has fueled the sudden rhetoric of Islamophobia in the United States of America and Europe?. After the attack of Twin Towers 9/11, Islam was being viewed as a conservative, barbaric and intolerant perspective of life. Muslim was posited as blood thirsty savages under the banner of a monolithic religion.The study aims to examine the impact of Islamophobia on society, attitudes, policies and the youths. Descriptive method with qualitative approach was used in the study. The 2016 Presidential elections of America were one of the most acrimonious and confrontational campaigns in the history of America. Extraordinary political rhetoric, outbursts in distasteful discriminatory tones, and anti-Muslim invectives blemished the campaign of United States (US) Presidential Elections of 2016. To endorse his political agenda, Donald J. Trump speciﬁcally focused upon Muslims as a grave issue, and likely toyed with the public pulses, which resulted in an unpredictable election result. Mirroring the perceived reality, media as an invention of information shapes public opinion. Media reports after 9/11 specifically underrepresented Muslim views and negatively portrayed Islamic culture. Islam was painted as a religion of discrimination, radicalization and regression by the Western media. With the advent of digital media, providing a carte blanche deserted the situation further. The rhetoric of Islamophobia dispersed hatred speech and acts of defamation on social media websites backed by the freedom of speech narrative.